Dynamics of Soil and Modelling of Geotechnical Problems Proceedings of Indian Geotechnical Conference 2020 Volume 5 - Satyanarayana Reddy, C. N. V.; Krishna, A. Murali; Satyam, Neelima; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book provides information on the latest technological developments taking place in Geotechnical engineering, pertaining to Soil Dynamics and Modelling of Geotechnical Problems. The book is useful for the academicians and working professionals with coverage of both theoretical and practical aspects of Dynamics of Soil and Modelling studies on Geotechnical problems based on research findings and site specific inputs. The book serves as a useful reference resource for graduate and postgraduate students of civil engineering and contents of the book are helpful to the postgraduate students and research scholars in carrying out the research.
Forensic Analysis of Retaining Wall Failure -- Numerical Analysis of Laterally Loaded Pile near Sloping Ground -- Optimization of Piled Raft on Sand for Plaza-Type Structures -- Numerical Analysis of Ring Foundation Fixed with Geogrid -- Parametric Study of Stone Column using PLAXIS 2D -- Effect of EPS Geofoam on Lateral Earth Pressure Reduction - A Numerical Study -- Seismic Performance of Open Ground Floor Tall Buildings on Flexible Ground -- Impact of Vibrations on a High Rise RCC Structure due to Blast Induced Demolition of Adjacent Building.
Keywords: Engineering geology; Building materials; Geotechnical engineering; Geoengineering; Building Materials; Geotechnical Engineering and Applied Earth Sciences; Geotechnical engineering -- Mathematical models -- Congresses; Soil dynamics -- Congresses